2014
DOI: 10.1016/j.jpainsymman.2013.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Patients' Sense of Security During Palliative Care—What Are the Influencing Factors?

Abstract: These findings stress the importance of palliative care services in supporting dying patients' sense of security through symptom management with a wide scope and through supporting the patients' sense of mastery, identity, and perception of a secure care interaction and also through attention to the family members' situation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
36
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 22 publications
(25 reference statements)
7
36
0
5
Order By: Relevance
“…Meeting different persons and having to repeat information or not having a trusted person to discuss care options with results in frustration (Klarare et al, ). Experiencing inclusion in care planning and being in a partnership helped patients and family caregivers continue with everyday life, as reported by patients with advanced cancer and family caregivers in this study and other studies (Melin‐Johansson et al, ; Milberg et al, ; Sarmento et al, ). Palliative care provision is complex, and appreciation of the highlighted nuances in this study may develop care further to better meet expressed or anticipated needs in patients with advanced cancer and their family caregivers.…”
Section: Discussionsupporting
confidence: 74%
“…Meeting different persons and having to repeat information or not having a trusted person to discuss care options with results in frustration (Klarare et al, ). Experiencing inclusion in care planning and being in a partnership helped patients and family caregivers continue with everyday life, as reported by patients with advanced cancer and family caregivers in this study and other studies (Melin‐Johansson et al, ; Milberg et al, ; Sarmento et al, ). Palliative care provision is complex, and appreciation of the highlighted nuances in this study may develop care further to better meet expressed or anticipated needs in patients with advanced cancer and their family caregivers.…”
Section: Discussionsupporting
confidence: 74%
“…In a multivariable analysis, Milberg et al 27 found that a sense of mastery over the situation was positively related to a higher sense of security.…”
Section: Discussionmentioning
confidence: 99%
“…A sense of security is reported to be an aspect of quality care [17] and a key component of palliative homecare [18][19][20][21]. Studies have revealed that patients and relatives' perceptions of security in homecare were fairly similar and encompassed a trusting relationship with the nurse, feeling respected, recognized, informed and being involved in the treatment and care [19,21]. It was also important to live as normal an everyday life as possible and that the healthcare professionals were reliable, competent and available when needed.…”
Section: Introductionmentioning
confidence: 99%